Efficacy and safety of volanesorsen in patients with multifactorial chylomicronaemia (COMPASS): a multicentre, double-blind, randomised, placebo-controlled, phase 3 trial. Issue 5 (May 2021) - Gouni-Berthold, Ioanna; Alexander, Veronica J; Yang, Qingqing; Hurh, Eunju; Steinhagen-Thiessen, Elisabeth; Moriarty, Patrick M; Hughes, Stephen G; Gaudet, Daniel; Hegele, Robert A; O'Dea, Louis St L; Stroes, Erik S G; Tsimikas, Sotirios; et al.
Summary: Background: Volanesorsen is an antisense oligonucleotide that targets hepatic apolipoprotein C-III synthesis and reduces plasma triglyceride concentration. The aim of this study was to explore the safety and efficacy of volanesorsen in patients with multifactorial chylomicronaemia syndrome. Methods: The COMPASS trial was a randomised, placebo-controlled, double-blind, phase 3 study done at 38 international clinical sites in Canada, France, Germany, the Netherlands, UK, and USA. Eligible patients were aged 18 years or older with multifactorial severe hypertriglyceridaemia or familial chylomicronaemia syndrome, who had a BMI of 45 kg/m 2 or less and fasting plasma triglyceride of 500 mg/dL or higher. Patients were randomly assigned (2:1) with an interactive response system using an allocation sequence and permuted block randomisation to receive subcutaneous volanesorsen (300 mg) or a matched volume of placebo (1·5 mL) once a week for 26 weeks. After 13 weeks of treatment, dosing was changed to 300 mg of volanesorsen or placebo every 2 weeks for all patients, except those who had completed 5 months or more of treatment as of May 27, 2016. Participants, investigators, sponsor personnel, and clinical research staff were all masked to the treatment assignments. The primary outcome was percentage change from baseline to 3 months in fasting triglyceride in the full analysis set (all patients who were randomly assigned and received at least one dose of study drug and had a baseline fasting triglyceride assessment). This trial is registered with ClinicalTrials.gov, NCT02300233 (completed). Findings: Between Feb 5, 2015, and Jan 24, 2017, 408 patients were screened for eligibility. 294 were excluded and 114 randomly assigned to receive either volanesorsen (n=76) or placebo (n=38). One patient in the volanesorsen group discontinued before receiving the study drug. The total number of dropouts was 28 (four in the placebo group and 24 in the treatment group). Volanesorsen reduced mean plasma triglyceride concentration by 71·2% (95% CI −79·3 to −63·2) from baseline to 3 months compared with 0·9% (−13·9 to 12·2) in the placebo group (p<0·0001), representing a mean absolute reduction of fasting plasma triglycerides of 869 mg/dL (95% CI −1018 to −720; 9·82 mmol/L [–11·51 to −8·14]) in volanesorsen compared with an increase in placebo of 74 mg/dL (−138 to 285; 0·83 mmol/L [–1·56 to 3·22]; p<0·0001). In the key safety analysis, five adjudicated events of acute pancreatitis occurred during the study treatment period, all in three of 38 patients in the placebo group. The most common adverse events were related to tolerability and included injection-site reactions (average of 24% of all volanesorsen injections vs 0·2% of placebo injections), which were all mild or moderate. One participant in the volanesorsen group had a platelet count reduction to less than 50 000 per μL and one patient had serum sickness, both of which were regarded as serious adverse events. Interpretation: Volanesorsen significantly reduced triglyceride concentrations in patients with multifactorial chlyomicronaemia and might reduce acute pancreatitis events in these patients. Funding: Ionis Pharmaceuticals and Akcea Therapeutics.